MEDICINE IN THE TIMURID ERA (BASED ON FRENCH SOURCES) - Abdinazarova Shahnoza Qalandarovna (Journals Park Publishing, 2022)
The article discusses the events of tibia and its development in the Timurid era on the example of the work of French thinkers.In order to cover the topic of the article, the French resource was widely used.
Keywords: medicine, Temurid, France, Marsel, Amir Timur.